Lietuvių bajorų požiūris į ketverių metų seimo reformas (pagal seimelių instrukcijas) - Raila, Egidijus (Lietuvos istorijos studijos, 1996)
The political and economical destruction in the Commonwealth was beginning to increase during the second part of the eighteenth century. The rather vague activity of the political structures was not able to restrain the arrogance of the boyars. On the other hand, the boyars themselves were not very keen on sacrificing their own interests for the sake of a strong centralized authority. August of 1788 brought election time to the local diets. The Lithuanian boyars had not a single leader at that time. Moreover, no one nobleman, during the local diets of 1788, had any kind of political program to introduce. The class requirements were predominant in the directions of these diets. The directions of the diets of 1790 did not change the real situation, although quite a large part of the Lithuanian boyars were already put up with the idea of the inevitable new laws, which were still hidden in numerous projects. The encouragement to introduce a new law about running the state could be found in many directions, without, however, making any visible changes in the existing liberty of the boyars.